Path-following control of small fixed-wing unmanned aircraft systems with H∞ type performance. (October 2017) - Muniraj, Devaprakash; Palframan, Mark C.; Guthrie, Kyle T.; Farhood, Mazen
Abstract: The focus of this paper is on the design of path-following controllers for a small fixed-wing unmanned aircraft system (UAS) using the H ∞ robust control framework. The robust controllers are synthesized based on a lumped path-following and UAS dynamics formulation, effectively combining the six degree-of-freedom aircraft dynamics with the established parallel transport frame virtual vehicle dynamics. Two path-following controllers with a conventional cascaded architecture consisting of an outer guidance loop and an inner stabilization loop are also considered as points of reference. The robustness and performance of these controllers are tested in a rigorousMATLAB simulation environment that includes steady winds, turbulence, measurement noise, and time delays. Finally, flight experiments are conducted on a small fixed-wing UAS platform, and the controllers are compared in terms of tracking performance, control effort, and ease of implementation.